Growth, agronomic characteristics and nutritional attributes of sorghum (Sorghum bicolor) genotypes resistant to ALS inhibitor herbicides. (7th June 2021) - Weerasooriya, Dilooshi K.; Bandara, Ananda Y.; Dowell, Floyd; Tesso, Tesfaye T.
Abstract: Resistance to acetolactate synthase (ALS) inhibitor herbicides discovered in wild relatives of sorghum was introgressed into cultivated types, but many of the derived lines display interveinal chlorosis at seedling stages. The objectives of this study were to examine the effect of chlorotic phenotype on growth and crop performance with and without herbicide application. Thirty‐six chlorotic and normal ALS‐resistant lines and susceptible check were evaluated in two experimental sets using randomized complete block design in split‐plot arrangement over a period of three years in four replications. Data were collected on leaf chlorophyll content, chlorophyll fluorescence, plant height, biomass and agronomic traits (days to anthesis, plant height and grain yield and yield components). Grain protein, starch, fat and ash were estimated using near‐infrared spectroscopy. The data showed interveinal chlorosis has significantly delayed flowering, but both chlorosis and herbicide treatment did not have negative effects on final yield and nutritional profile. The study suggests ALS‐resistant sorghums with minimal yellowing effect can be developed, and the trait can be commercially deployed without drawback on yield and utilization attributes.